2017
DOI: 10.3847/1538-4357/aa7af0
|View full text |Cite
|
Sign up to set email alerts
|

Inversions for Deep Solar Meridional Flow Using Spherical Born Kernels

Abstract: The solar meridional flow is a crucial ingredient in modern dynamo theory. Seismic estimates of this flow have, however, been contradictory in deeper layers below about 0.9 R . Results from timedistance helioseismology have so far been obtained using the ray approximation. Here, we perform inversions using the Born approximation. The initial result is similar to the result previously obtained by Jackiewicz et al. (2015) using ray kernels while using the same set of GONG data and the SOLA inversion technique. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
4
24
2
Order By: Relevance
“…It is important no mention that the current results of the helioseismic inversions for the meridional circulation remains controversial For example, Rajaguru and Antia [72] found that the meridional circulation can be approximated by a single-cell structure with the return flow deeper than 0.77R . However, their results indicate an additional weak cell in the equatorial region, and contradict to the recent results of Böning et al [5] who confirmed a shallow return flow at 0.9R . Also, their results indicated that the upper meridional circulation cell extends close to the solar pole.…”
Section: The Angular Momentum Balancecontrasting
confidence: 93%
“…It is important no mention that the current results of the helioseismic inversions for the meridional circulation remains controversial For example, Rajaguru and Antia [72] found that the meridional circulation can be approximated by a single-cell structure with the return flow deeper than 0.77R . However, their results indicate an additional weak cell in the equatorial region, and contradict to the recent results of Böning et al [5] who confirmed a shallow return flow at 0.9R . Also, their results indicated that the upper meridional circulation cell extends close to the solar pole.…”
Section: The Angular Momentum Balancecontrasting
confidence: 93%
“…On closer inspection, this may incur an uncertainty of 0.01-0.03 s, for short distances in particular (see Appendix D). In this regard, a sophisticated inversion with kernels that take into account finite-wavelength effects (e.g., Böning et al 2017;Gizon et al 2017;Fournier et al 2018;Mandal et al 2018) is needed to correctly decipher the meaning of the measured traveltime shifts. It would be preferable to study the north-south asymmetry and other fine structures of meridional circulation by inversion instead of forward modeling.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, a number of inconsistent helioseismic results were reported (Zhao et al 2013;Schad et al 2013;Jackiewicz et al 2015;Rajaguru & Antia 2015;Böning et al 2017;Chen & Zhao 2017;Lin & Chou 2018). The main reason is that helioseismic measurements suffer from a variety of systematic errors such as instrumental misalignment, the center-to-limb variation, and the influence of the surface magnetic field (e.g., Beck & Giles 2005;Zhao et al 2012;Liang & Chou 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…In that case, we can only obtain an average meridional flow profile for the time period of the analysis. Improvements such as including full covariance matrix as Böning et al (2017) have suggested and accounting for line-of-sight effects (latter is only possible in wave-theoretic approach) is reserved for our future studies.…”
Section: Discussionmentioning
confidence: 99%